Batatamba As A Local Healing Tradition In The Banjar Community Of Kalimantan: Mantras, Mediums, Rituals And Continuity - Abidin, Muhammad Zainal; Arni; Mulyani; Taufik, Muhammad (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2024)
This article examines the Batatamba tradition among the Banjar community in Kalimantan, focusing on its mantras, mediums, rituals, and continuity. The Banjar community is known for its strong connection to Sufi traditions, which are notably inclusive of local customs. One such local tradition is Batatamba, which seeks to integrate religious language with indigenous culture. The article employs an anthropological approach to analyze the cultural aspects of this tradition, treating them as central to the study. The choice of an anthropological perspective allows for a deeper exploration of the interaction between cultural and religious elements within the Batatamba practice. The findings indicate that Banjar Islam has emerged from a process of acculturation, blending Islamic teachings with various local traditions, religions, and beliefs, a process that is especially evident in the Batatamba tradition. This integration can be observed in practices such as the recitation of mantras that combine Quranic verses with local invocations, or the incorporation of the Islamic declaration